EFFICACY OF ORAL PREDNISOLONE IN MANAGEMENT OF BRONCHIOLITIS: A PLACEBO-CONTROLLED STUDY - TAJ , F; BATOOL , M; KHIZER , M (Biological and Clinical Sciences Research Journal, 2023)
Acute bronchiolitis is a common and deadly condition in infants described as a respiratory infection due to inflammatory obstruction of bronchioles. This study was designed to assess prednisolone's efficacy in treating bronchiolitis in children aged >2 years. A retrospective study was conducted in the Department of peadiatrics in different hospitals from February 2022- February 2023. A total of 80 children aged > 2 years with acute bronchiolitis were included in the study. The patients were divided into groups A and B. Group A (n=40) was administered salbutamol combined with prednisolone, and Group B (n=40) was administered salbutamol alone. The outcomes of both treatments were evaluated. The average age in group A and B was 6.9± 4.5 months and 5.5 ± 3.9 months, respectively. 65 patients (81.2%) belonged to middle-class families, and 20 (25%) came from crowded households. 10 patients (12.5%) had a preterm delivery, and 12 (15%) had low birth weight. A significant difference was observed in Group A after 3 days of treatment (p <0.05), and a reduction in hospital stay was also noted (p<0.001) in contrast with Group B. Based on the results, it can be concluded that the prednisolone is an effective drug in the management of bronchiolitis by reducing hospital stay and disease severity in children > 2 years.